Sub–Hepatic Caecum - Nagashree M V; Gireesh; Lakshmi Prabha Subhash; Veena Pai (Journal of Clinical and Diagnostic Research, 2013)
Malrotation of gut is an intestinal gestational disorder which not only affects the positioning of the midgut, but also its vascular supply. It usually presents with the syndrome of bouts of colic and vomiting with little distention of abdomen and diarrhea. Though midgut malrotation is a common cause of intestinal obstruction in newborn, scant attention is given to this developmental anomaly as a cause of symptoms in adults. The development of midgut portion of alimentary canal suffers a large variety of variations. The surgical importance of abdominal situation of the portions of intestine derived from the midgut loop requires little attention. Sub–hepatic anatomical location of the appendix makes it more difficult to diagnose acute appendicitis at any age, including in older adults. Failure to recognize the nature and characteristic features of these misplacements may lead to grave errors in procedure, or to injurious prolongation of the operation. Here in we found a rare abnormality of caecum, which was present in the sub hepatic region with the absence of ascending colon during routine dissection classes for undergraduate students.